Odzwierciedlenie dwu postaw wobec pandemii w koronapolszczyźnie na przykładzie nazw koronawirusa SARS-CoV-2 - Piotrowicz-Krenc, Anna; Witaszek-Samborska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article concerns the names of the SARS-CoV-2 coronavirus used during the COVID-19 pandemic by Polish speakers representing two attitudes towards the threat – rationalists, who believe in the existence of the pandemic and respect the introduced restrictions, and negationists, who deny the existence of the pandemic and oppose the introduction of restrictions. The research material consists of internet texts collected by the authors in a database created while working on the book Koronapolszczyzna. Słownictwo czasu pandemii koronawirusa SARS-CoV-2 (Coronapolish. Vocabulary of the SARS-CoV-2 Coronavirus Pandemic) published in Poznań in 2024. It turned out that both emotionally neutral lexemes, used mainly by rationalists, and expressive vocabulary functioned as names for the SARS-CoV-2 coronavirus. In terms of emotionally-tinged names, negationists created primarily words with a dismissive, contemptuous meaning and vulgarisms, while rationalists created words with a humorous meaning. All expressive words played a causative role during the pandemic – they were intended to help people come to terms with the difficult reality.